Critical role of thulium metal interlayer in ultra-low contact resistance reduction in Ni-InGaAs/n-InGaAs for n-MOSFETs. (August 2019) - Eadi, Sunil Babu; Lee, Jeong Chan; Song, Hyeong-Sub; Oh, Jungwoo; Lee, Hi-Deok
Abstract: In this Letter, Thulium (Tm) interlayer was applied at the junction of Ni-InGaAs/n- In0.53 Ga0.47 As and specific contact resistivity ( ρc ) was derived at the junction using circular transmission line model (CTLM) procedure. The contact resistance values obtained using the CTLM were 1.65 × 10 −8 and 2.11 × 10 −6  Ω cm 2 for a 5 nm thick Tm interlayer sample and the reference sample (without the Tm interlayer), respectively. The finding shows a drastic decrease in contact resistance and Tm interlayer reduce the contact resistance by more than two orders of magnitude compared to the reference sample. The surface and structural properties of Ni-InGaAs with Tm interlayer were characterized using XRD, FE-SEM and TEM and the elemental depth profile using SIMS analysis. Highlights: Contact resistance obtained in this study is significantly lower than that reported for Ni-InGaAs/n-InGaAs junctions. Specific contact resistivity of 1.65 × 10 −8  Ω cm 2 was achieved of Ni-InGaAs/n-InGaAs by introducing thulium as an interlayer. New alloy Tm/Ni-InGaAs could lower work function and enhance dopant pile-up near interface of Ni-InGaAs/n-In0.53Ga0.47As. Introducing Tm interlayer aids in controlled formation of Ni-InGaAs and makes the interface of Ni-InGaAs/InGaAs smooth.